(untitled) (Research, Society and Development, 2022)
The Brazilian Amazon has been the subject of global debates around the importance of its assets for the maintenance of global ecosystem services. In addition to environmental degradation, there are low indicators of social development. The purpose of the investigation was to analyze whether the resources arising from the Financial Compensation for the Exploration of Mineral Resources (CFEM) are related to the economic and socio-environmental development of the municipalities of the State of Pará. The sample comprised the years 2005 to 2016. Pearson correlation analysis and linear regression were performed with results later collated by the theory/hypothesis of the Curse of Natural Resources. It was found that the hypothesis of the Curse of Natural Resources did not fully adhere to the results of the study, as the municipalities that receive the highest amount of royalties tend to have better socioeconomic conditions, as well as higher expenses related to environmental management. However, a tendency towards clientelistic practices was observed, which indicates a possible use of resources in electoral processes. The implications of the study indicate the need to develop an accountability mechanism to improve the social control of the resources used by the transfers. Although the effects of CFEM are positive, the design of public policies on transfers must be balanced against the social, economic and environmental vulnerabilities of Amazonian territories.